ENHANCING STRENGTH: FIBERREINFORCED POLYMER COMPOSITES IN PLAIN CEMENT CONCRETE BEAMS - Sruthi, Thirunagiri; Sudhakar, Eslavath; Krishna Prasad, Lakavath; Sai Jyothi, Kakati Sri (International Journal of Psychosocial Rehabilitation, 2019)
There is now a lot of research being done on the possible applications of fiber-reinforced polymer wraps, covers, and sheets for the preservation and protection of metropolitan populations. It has been demonstrated that treating ageing structures using fiber-reinforced polymer (FRP) is a great method of strengthening and repairing them. FRP repair solutions offer a more affordable option than traditional repair techniques and materials. Regular beams’ flexural and shear behaviour have been studied using glass fibre reinforced polymer (GFRP) sheets. GFRP sheets reinforced with epoxy were used in a balanced two-point manner to test cement footings built remotely until they failed. Three sets of samples were prepared for this RCT (randomised controlled experiment). In SET I, two flexure cubes were cast and reinforced with continuous sheets of glass fibre reinforced polymer (GFRP), while one weak cube served as a control. SET II controlled the behaviour of the third shear-weak cylinder and improved the shear characteristics of two of the cylinders using continuous glass fibre reinforced polymer (GFRP) sheets. In SET III, three flexure-weak prisms were cast, two of which were strengthened with glass fibre reinforced polymer (GFRP) sheets and one of which functioned as the controlled beam. To reinforce or repair the samples, different configurations and amounts of GFRP sheets and resins are utilised. Furthermore, tensile strength is tested following the casting of twelve cylinders, three of which are retrofitted with glass fibre reinforced polymer (GFRP) sheets, and one of which is used as a control. In a controlled laboratory context, the load, deflection, and possible failure modes of each beam were determined. There is also a thorough discussion of the creation and application of GFRP sheets for reinforcing RC beams. The relationship between beams’ ultimate load-bearing capability and failure mechanism and the amount of GFRP layers employed in their manufacture is examined. There is now a lot of research being done on the possible applications of fiber-reinforced polymer wraps, covers, and sheets for the preservation and protection of metropolitan populations. It has been demonstrated that treating ageing structures using fiber-reinforced polymer (FRP) is a great method of strengthening and repairing them. FRP repair solutions offer a more affordable option than traditional repair techniques and materials. Regular beams’ flexural and shear behaviour have been studied using glass fibre reinforced polymer (GFRP) sheets. GFRP sheets reinforced with epoxy were used in a balanced two-point manner to test cement footings built remotely until they failed. Three sets of samples were prepared for this RCT (randomised controlled experiment). In SET I, two flexure cubes were cast and reinforced with continuous sheets of glass fibre reinforced polymer (GFRP), while one weak cube served as a control. SET II controlled the behaviour of the third shearweak cylinder and improved the shear characteristics of two of the cylinders using continuous glass fibre reinforced polymer (GFRP) sheets. In SET III, three flexure-weak prisms were cast, two of which were strengthened with glass fibre reinforced polymer (GFRP) sheets and one of which functioned as the controlled beam. To reinforce or repair the samples, different configurations and amounts of GFRP sheets and resins are utilised. Furthermore, tensile strength is tested following the casting of twelve cylinders, three of which are retrofitted with glass fibre reinforced polymer (GFRP) sheets, and one of which is used as a control. In a controlled laboratory context, the load, deflection, and possible failure modes of each beam were determined. There is also a thorough discussion of the creation and application of GFRP sheets for reinforcing RC beams. The impact of multiple GFRP layers on the ultimate load-bearing capacity and failure mechanism of the beams is discussed